ОСТЕОПОРОЗ В ОБЩЕТЕРАПЕВТИЧЕСКОЙ ПРАКТИКЕ: ОТ ДИАГНОСТИЧЕСКОЙ ГИПОТЕЗЫ – К ДИФФЕРЕНЦИАЛЬНОМУ ДИАГНОЗУ - A. A. Muradyants; N. A. Shostak (Klinicist)
Osteoporosis and related fractures are one of the major causes of disability and premature death in the elderly. The timely diagnosis of osteoporosis is the basis of effective therapy in the patients. The paper presents approaches to diagnosing osteoporosis, its primary and secondary forms, as well as its differential diagnosis with other skeletal diseases.